Nebulised 3% hypertonic saline versus 0.9% saline for treating patients hospitalised with acute bronchiolitis: protocol for a randomised, double-blind, multicentre trial - Sara Szupieńko; Aleksandra Buczek; Henryk Szymański (BMJ Open)
Introduction Bronchiolitis is an acute viral infection of the lower respiratory tract. It is most commonly caused by respiratory syncytial virus. Being a common reason for hospitalisation, it affects 13–17% of all hospitalised children younger than 2 years. Only supportive therapy, including suctioning nasal secretions, water–electrolyte balance maintenance and oxygen supplementation when needed, is recommended. However, non-evidence-based diagnostic and therapeutic approaches, including the use of inhaled bronchodilators, nebulised epinephrine, and nebulised and systemic steroids, are common. The inhalation of 3% hypertonic saline is not recommended in bronchiolitis management. However, a recently published meta-analysis revealed that the inhalation of hypertonic saline can reduce the risk of hospitalisation for outpatients with bronchiolitis, while resulting in a shorter length of hospital stay and reduced severity of respiratory distress for inpatients, although the evidence is of low certainty. We aim to assess the efficacy of nebulised hypertonic saline for the treatment of children hospitalised with bronchiolitis.Methods and analysis This will be a randomised, double-blinded, parallel-group, controlled trial. Children younger than 2 years who are hospitalised due to bronchiolitis will be recruited from at least three paediatric departments in Poland. Bronchiolitis is defined as an apparent viral respiratory tract infection associated with airway obstruction that is manifested by at least one of following symptoms: tachypnoea, increased respiratory effort, crackles and/or wheezing. A total of 140 children will be randomised (1:1) to receive either hypertonic saline nebulisation (5 mL, three times a day) or normal saline at the same dose. The primary outcome measure will be the duration of hospitalisation.Ethics and dissemination The Bioethics Committee of the Lower Silesia Medical Chamber in Wroclaw approved the study protocol (4/PNDR/2023). Caregivers will receive oral and written information about the study and written informed consent will be obtained by the study physicians. The findings of the study will be submitted to a peer-reviewed journal, and abstracts will be submitted to relevant national and international conferences.Trial registration number ClinicalTrials.gov Registry (NCT06069336).